Review: Virulence Factors, Resistance Genes and Pathogenicity of Moraxella Catarrhalis - Lubana Hamoud Shamkhi Alai; Zainab Falah Hassan Jassim; Roaa Mohammed Hasan Ahmed; Aya Najimaldin Ahmed Ibrahim (American Journal of Biology and Natural Sciences, 2025)
Moraxella catarrhalis is an opportunistic human pathogen responsible for respiratory tract infections, particularly in individuals with chronic obstructive pulmonary disease (COPD). Despite its clinical significance, knowledge gaps persist regarding its virulence mechanisms and resistance factors. This study reviews key virulence factors, including adhesion proteins and biofilm formation mechanisms, as well as antibiotic resistance genes, such as bro-1, bro-2, and mcr genes, which contribute to multidrug resistance. The research utilized a literature review approach to analyze the bacterium’s pathogenicity and antimicrobial resistance. Findings indicate that M. catarrhalis employs various strategies to evade the immune system and resist antibiotic treatment, posing challenges to clinical management. The results highlight the necessity of targeted therapeutic approaches and vaccine development to mitigate the impact of M. catarrhalis-related infections. These insights contribute to a better understanding of bacterial resistance trends, ultimately aiding in the development of more effective treatment strategies.